Self-Esteem, Social Support, and Resilience among Indonesian Female Peacekeepers - Arbiansyah Tri Panca Titis; Mukminin Emha Zainul; Guritna Emanuel Taru; Zhafira (Research Synergy Foundation, 2026)
Peacekeeping personnel play a strategic role in maintaining international peace, security, and stability in conflict-affected regions. Following the adoption of United Nations Security Council Resolution 1325, the participation of women in peacekeeping operations has received increasing global attention, emphasizing the importance of strengthening psychological resources that enable female peacekeepers to effectively adapt to challenging and high-risk operational environments. Indonesian female peacekeepers serving in United Nations missions are required not only to demonstrate professional military competence but also to maintain resilience in coping with operational stress, exposure to violence, prolonged family separation, and complex sociocultural conditions. This study aimed to examine the effects of self-esteem and social support on resilience among Indonesian female peacekeepers deployed in United Nations peacekeeping missions. A quantitative cross-sectional design was employed, using Structural Equation Modeling (SEM) in AMOS to analyze data from 112 Indonesian female peacekeepers. The findings revealed that self-esteem has a statistically significant positive effect on resilience (beta = 0.97, p < 0.05), whereas social support did not significantly predict resilience (beta = -0.02, p > 0.05). The measurement model has an acceptable level of goodness of fit, particularly on the RMSEA, CFI, and TLI indices, although GFI and AGFI indicate the need for further model refinement. These findings highlight self-esteem as a critical psychological resource that enhances resilience among Indonesian female peacekeepers. Therefore, psychological intervention programs focusing on self-esteem enhancement, adaptive coping strategies, and personal psychological strengths are recommended to improve psychological well-being, adaptability, and operational effectiveness in peacekeeping missions.